2018
DOI: 10.1007/s12035-018-1261-z
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Deletion of Soluble Epoxide Hydroxylase Causes Anxiety-Like Behaviors in Mice

Abstract: Soluble epoxide hydrolase (sEH), an enzyme with COOH-terminal hydrolase and NH-terminal lipid phosphatase activities, is expressed in regions of the brain such as the cortex, white matter, hippocampus, substantia nigra, and striatum. sEH is involved in the regulation of cerebrovascular and neuronal function upon pathological insults. However, the physiological significance of sEH and its underlying mechanism in modulating brain function are not fully understood. In this study, we investigated the role of sEH i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…2-4). One recent study showed that sEHÀ/À mice displayed anxiety-like behaviors without clear molecular and neural circuit mechanisms (Lee et al, 2019). Together, these findings demonstrated a novel role for sEH in the regulation of anxiety and might extend the function of the ARA-EET pathway in the brain.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…2-4). One recent study showed that sEHÀ/À mice displayed anxiety-like behaviors without clear molecular and neural circuit mechanisms (Lee et al, 2019). Together, these findings demonstrated a novel role for sEH in the regulation of anxiety and might extend the function of the ARA-EET pathway in the brain.…”
Section: Discussionmentioning
confidence: 91%
“…The P450 epoxygenase pathway metabolizes ARA to hydroxyeicosatetraenoic acids (n-HETEs) and epoxyeicosatrienoic acids (EETs; Harris and Hammock, 2013;Morisseau and Hammock, 2013;Atone et al, 2020). Soluble epoxide hydrolase (sEH), a key enzyme that catalyzes the degradation of EETs, is involved in anorexia nervosa and mood disorders (Scott-Van Zeeland et al, 2014;Ren et al, 2016;Lee et al, 2019;Xiong et al, 2019). In the prefrontal cortex, sEH is mostly localized in astrocytes and regulates depressivelike behaviors (Marowsky et al, 2009;Xiong et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…These differential associations are likely due to significant between-group differences in anxiety severity, variability in the postprandial increase in sEH, and sample size difference at the postprandial timepoint. Two studies using animal models have suggested that sEH may play a role in anxiety, as sEH knock-out induced anxiety-like behaviors [ 62 , 63 ]. Further work is needed to understand the link between sEH and anxiety, especially in human patients.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies using patients with depression and animal models of depression have reported elevated sEH under chronic stress and depressive conditions [ 58 , 59 , 60 ]. An sEH knock-out model and sEH downregulation have both shown anti-depressive and anxiety-modulating effects in animal models [ 59 , 60 , 61 , 62 , 63 , 64 ], implying that sEH may contribute to the etiology of depression and anxiety.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the phosphorylation of CaMKII can be regulated via various receptors or enzymes. Mice without soluble epoxide hydroxylase exhibit anxiety-like behavior as a result of the hyperphosphorylation of CaMKII and glycogen synthase kinase 3 α/β (GSK3α/β) [ 185 ]. Moreover, the decreased level of CaMKII in the striatum was observed in mice without connexin36; the protein presents in gap junctions between interneurons in several brain structures [ 186 ].…”
Section: Anxiety-like State In Rodentsmentioning
confidence: 99%